Consonant length as expressive resource in sung Spanish - Guzmán, Mariano Nicolás (2018)
A review of 19th-century Spanish literature on vocal pedagogy (Guzmán, Shifres & Carranza, 2017) found that in classical singing the pronunciation of Spanish is subordinated to an aesthetic canon, which limits the expressive range of speech. According to this canon, vowels have a leading role since they can be sustained, while consonants must be articulated “clearly” but “marked”. Due to these requirements, consonants must be shortened in classical singing (Miller, 1996), which ignores the variability of segmental length in spoken Spanish (Mendoza et al., 2003) and its identity effects on communication (Carter & Wolford, 2016). Although recent studies compare the expressiveness in speaking and singing (Scherer et al., 2015), the scope of consonant length as expressive resource in sung Spanish is still unknown.